The Evolution of an AgI Cloud‐Seeding Track in Central China as Seen by a Combination of Radar, Satellite, and Disdrometer Observations. Issue 11 (27th May 2021) - Wang, Jin; Yue, Zhiguo; Rosenfeld, Daniel; Zhang, Lei; Zhu, Yannian; Dai, Jin; Yu, Xing; Li, Jinhui
Abstract: Operational cloud seeding has been implemented to alleviate local precipitation shortages in China for over half a century. Here, we present quantitative evidence for the effect of AgI seeding on supercooled layer clouds with a top cloud temperature of −15°C in China, as documented for the first time by a combination of radar, satellite, and disdrometer observations. A radar signature appeared 18 min after seeding, shortly followed by a visible glaciated seeding track. The seeding signature expanded horizontally at a rate of ∼1.4 and ∼0.3 m s −1 before and after 04:25 UTC. The radar signature descended to the surface 40 min after seeding. A disdrometer captured the precipitation of the first seeded raindrops that reached maximum diameter of 2.75 mm compared to the maximum diameter of 1 mm of the light background rain. The enhanced surface rainfall was observed within the subsequent 100 min. A conceptual model for the formation and expansion of the seeding track is presented. Although the precipitation was light, it is a promising step toward the goal of quantifying the impact of cloud seeding in China. Key Points: The evolution of an AgI seeding track was documented by a combination of radar, satellite, and laser raindrop disdrometer observations The radar signature appeared 18 min after seeding, expanded at a rate of 1.4 m s −1 for 90 min while splitting into a double band A conceptual model of the evolution of the seeded clouds and precipitation is presented